Scalable fault tolerant architecture for complex event processing systems - Randika, H.C.; Martin, H.E.; Sampath, D.M.R.R.; Metihakwala, D.S.; Sarveswaran, K.; Wijekoon, M. (IEEE, 2010)
Complex Event Processing (CEP) is one of the fastest emerging fields in computer science. Modern CEP systems which are critical for organizations to maintain their business processes and to achieve excellence through operational responsiveness should be scalable and fault tolerant. The research project epZilla is to build a highly scalable, highly available, real time, fault tolerant distributed architecture for CEP systems.